CRITICAL PARAMETERS OF TUNNEL POSITIONING IN ACL RECONSTRUCTION: A RETROSPECTIVE MRI ANALYSIS - Kostrub, Oleksandr; Didukh, Petro; Nikiforova, Iryna; Zasadnyuk, Ivan; Blonskyi, Roman; Podik, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Anterior cruciate ligament (ACL) rupture is one of the most common knee injuries requiring surgical intervention. The increasing number of revision surgeries indicates the potential presence of technical errors during primary reconstruction, emphasizing the importance of outcome analysis and careful surgical planning. MRI remains the gold standard not only for diagnosing ACL injuries and associated lesions, but also for evaluating postoperative changes. Objective. To assess MRI-based measurements of femoral and tibial tunnel inclination and entry point location as potential technical causes of ACL graft failure. Methods. A retrospective analysis was conducted on 105 knee MRI scans from patients following primary ACL reconstruction. The parameters evaluated included femoral and tibial tunnel inclination angles on coronal views, femoral tunnel entry point using a modified Bernhard and Hertel method, and tibial tunnel entry point assessed via he Amis and Jacob line. Results. A femoral tunnel angle within the 30°–50° range was found in 63 % of cases, with the optimal range of 32°– 39° observed in 21 %. In 16 % of cases, the angle exceeded 50°, and in 3 % it was less than 17°. The femoral tunnel entry point fell within the normal range in 46 % of cases, while in 42 cases it was located outside the defined measurement rectangle. Tibial tunnel position on sagittal projection was anatomically correct in 38 % of cases, anteriorly displaced in 21 %, and posteriorly displaced in 41 %. The optimal tibial tunnel inclination angle (≥ 65°) was found in 61 % of cases. Graft integrity was preserved in 24 % of cases with posterior tibial tunnel positioning, and in only 6 % with anterior placement. Conclusions. Technical errors in tunnel formation are a common cause of ACL graft failure. Accurate determination of the tunnel entry point is the most critical factor, while tunnel angle plays a secondary, yet diagnostically valuable, role. These findings highlight the need for meticulous planning, including the use of MRI and intraoperative navigation techniques to optimize tunnel placement.